Zur Massenvermehrung, Lebensweise und Möglichkeit einer biologischen Bekämpfung der Kiefernnadelgallmücke Thecodiplosis brachyntera Schwaegr. (Diptera: Cecidomyiidae). - Fankhänel, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1962)
In some districts of the German Democratic Republic - especially on poor sandy ocalities N and SW of Berlin - during 1959 to 1961 an outhbreak of the gall midge Thecodiplosis brachyntera Schwaegr. accumulated to a higher extent. There are given results of the investigations made on the life history of the gall midge, especially on the phenology of flight period and larval development. The lenght of larvae and infested pine needles show distinct differences dependent on the time of investigation during the vegetation period and the position of the young shoots on the tree. The Scelionid species Misocyclops pini Kieff., which is adapted to the life history of its host, has proved an effective endoparasite of the gall midge and could finish an outbreak of Th. brachyntera by means of parasitization up to 80-95% for instance in the district of Neuruppin. The determination of the proportion gall midge: parasite was found valuable to ascertain the further progress of the outbreak and may offer the possibility to control this pest by means of innerareal removal of the parasite Misocyclops pini Kieff.